Adsorption of Copper and Arsenic from Water Using a Semi-Interpenetrating Polymer Network Based on Alginate and Chitosan - Sanchez-Poblete, J; Alsamman-, M (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
New biobased hydrogels were prepared via a semi-interpenetrating polymer network (semi-IPN) using polyacrylamide/chitosan (PAAM/chitosan) hydrogel for the adsorption of As(V) or poly acrylic acid/alginate (PAA/alginate) hydrogel for the adsorption of Cu(II). Both systems were crosslinked using N,N′-methylenebisacrylamide as the crosslinker and ammonium persulfate as the initiating agent. The hydrogels were characterized by SEM, Z-potential, and FTIR. Their performance was studied under different variables, such as the biopolymer effect, adsorbent dose, pH, contact time, and concentration of metal ions. The characterization of hydrogels revealed the morphology of the material, with and without biopolymers. In both cases, the added biopolymer provided porosity and cavities’ formation, which improved the removal capacity. The Z-potential informed the surface charge of hydrogels, and the addition of biopolymers modified it, which explains the further metal removal ability. The FTIR spectra showed the functional groups of the hydrogels, confirming its chemical structure. In addition, the adsorption results showed that PAAM/chitosan can efficiently remove arsenic, reaching a capacity of 17.8 mg/g at pH 5.0, and it can also be regenerated by HNO3 for six cycles. On the other hand, copper-ion absorption was studied on PAA/alginate, which can remove with an adsorption capacity of 63.59 mg/g at pH 4.0, and the results indicate that it can also be regenerated by HNO3 for five cycles. © 2023 by the authors.